2009
DOI: 10.1002/joc.2044
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization signature in the observed heavy rainfall climatology over India

Abstract: ABSTRACT:We assess the urbanization impacts on the heavy rainfall climatology during the Indian summer monsoon. While a number of studies have identified the impact of urbanization on local precipitation, a large-scale assessment has been lacking. This relation between urbanization and Indian monsoon rainfall changes is investigated by analyzing in situ and satellite-based precipitation and population datasets. Using a long-term daily rainfall dataset and high-resolution gridded analysis of human population, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
183
3
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(196 citation statements)
references
References 37 publications
6
183
3
4
Order By: Relevance
“…The effect of urban-induced rainfall was observed in northern Bangladesh (Yamane et al 2010) and urban areas in India (Kishtawal et al 2010;Mitra et al 2012;Vittal et al 2013). Both Shillong (the capital of Meghalaya with a population of 350,000 in 2011) and Gauhati (the capital of Assam with a population of 968,000 in 2011) are two of the most rapidly growing cities in India during the second half of the twentieth century.…”
Section: Propagation Of the High Rainfallmentioning
confidence: 99%
“…The effect of urban-induced rainfall was observed in northern Bangladesh (Yamane et al 2010) and urban areas in India (Kishtawal et al 2010;Mitra et al 2012;Vittal et al 2013). Both Shillong (the capital of Meghalaya with a population of 350,000 in 2011) and Gauhati (the capital of Assam with a population of 968,000 in 2011) are two of the most rapidly growing cities in India during the second half of the twentieth century.…”
Section: Propagation Of the High Rainfallmentioning
confidence: 99%
“…Mitra et al (2012) analyzed premonsoonal rainfall over a megalopolis in India and identified the possible association between urban land cover expansion and premonsoonal rainfall increase. Urbanization effects on heavy rainfall during the Indian summer monsoon were assessed by Kishtawal et al (2010) with in situ and satellite-based precipitation. They found a significant increasing trend in the frequency of heavy rainfall over the urban regions of India during the monsoon season.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been considerable interest in evaluating temperature differences between urban areas and their rural surroundings [3,[9][10][11][12][13][14], studies of variations in long-term precipitation due to urbanization [6,15,16] or other changes in land use and land cover (LULC), such as deforestation/afforestation, are limited [4]. Deforestation can result in albedo increases, reduction of evapotranspiration (which changes sensible and latent heat partitioning), and rainfall interception [15].…”
Section: Introductionmentioning
confidence: 99%